Avifaunal diversity of Northwestern Himalayas (Jammu and Kashmir) and Trans Himalayas (Ladakh) of India - PARVAIZ YOUSUF; SEMRAN PARVAIZ; NISHEET ZEHBI; SABIA ALTAF; BILAL NASIR ZARGAR; ROUF RATHER; JAVEED TANTRAY; MOHAMMAD LATEEF (Smujo International, 2023)
Abstract. Yousuf P, Parvaiz S, Zehbi N, Altaf S, Zargar BN, Rather R, Tantray J, Lateef M. 2023. Avifaunal diversity of Northwestern Himalayas (Jammu and Kashmir) and Trans Himalayas (Ladakh) of India. Biodiversitas 24: 212-231. The Himalayas are home to various plants and animals, making it one of the world's most biodiverse regions. The northwestern Himalayan region of the trans-Himalayan Region of Ladakh and Jammu and Kashmir, India are home to various bird species due to varied topography and temperature. In this study, we collected the checklists and field data for 3 years based on compiling data from published and unpublished scientific literature, print and electronic, currently accessible in research articles, papers, books, websites, web pages, and field notes. The trans-Himalayas (Ladakh) and Northwestern Himalayas (Jammu and Kashmir) are home to 677 bird species, which belong to 89 families; there are approximately 107 families in the Indian sub-continent, equals to 6.77% of total bird species (>10,000) found globally and 49.2% of total bird species (1,376) in the Indian subcontinent. The family Muscicapidae (53 or 7.8%) has the most species, followed by Accipitridae (41 or 6%), and so on. Furthermore, the threatened species number is 54 (8%), which includes 23 (3.40%), 22 (3.25%), 6 (0.8%), and 3 (0.44%) under Vulnerable, Near Threatened, Endangered, and critically Endangered categories. Moreover, among 677 species, 228 species (33.77%) are found in all the 3 regions, 77 (11.4%) in only Jammu & Kashmir but not Ladakh, 24 (3.55%) in Jammu & Ladakh but not in Kashmir, 152 (22.5%) only in Jammu but not in Kashmir & Ladakh, 80 (11.85%) in Kashmir & Ladakh but not in Jammu, 26 (3.84%) only in Kashmir but not in Jammu & Ladakh, 71 (10.51%) only in Ladakh but not in Jammu & Kashmir. This information could provide these regions first-of-its-kind comprehensive data on bird diversity.